2021
DOI: 10.7150/ijms.49449
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Six Autophagy-related Long Non-coding RNAs as Prognostic Signature in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a commonly occurring tumour with poor prognosis. Autophagy-related long non-coding RNAs (lncRNAs) have received much attention as biomarkers for cancer prognosis and diagnosis. However, few studies have focused on their prognostic predictive value specifically in CRC. This research aimed to construct a robust autophagy-related lncRNA prognostic signature for CRC. Autophagy-related lncRNAs from The Cancer Genome Atlas database were screened using univariate Cox, LASSO, and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…In this study, some of the irlncRNAs in the process of modeling that have been already identi ed play an important role in malignant phenotypes of various cancer types, such as LINC01063 [24,25], HOXC-AS1 [26,27], LINC02454 [28,29] and SCAT1 [30]. Furthermore, previous reports have shown that LINC00460 [31], C5orf66-AS1 [32] and TMPO-AS1 [33] are associated with prognosis and treatment outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 75%
“…In this study, some of the irlncRNAs in the process of modeling that have been already identi ed play an important role in malignant phenotypes of various cancer types, such as LINC01063 [24,25], HOXC-AS1 [26,27], LINC02454 [28,29] and SCAT1 [30]. Furthermore, previous reports have shown that LINC00460 [31], C5orf66-AS1 [32] and TMPO-AS1 [33] are associated with prognosis and treatment outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 75%
“…According to the KM survival analysis, the autophagy-associated genes EPHB2, NOL3, and SNAI1 in the prognostic model were statistically significant (p < 0.05). EPHB2 encodes the receptor tyrosine kinase transmembrane glycoprotein family member EPHB2, which engages in lots of cellular processes including movement, division, and differentiation ( 27 ). EPHB2 functions in the gastrointestinal homeostasis and is an essential factor regulating the classification of mature epithelial cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human breast cancer have shown that the expression of EPHB2 can induce the increase of ATG5/12 and LC3II, thereby inducing autophagy ( 26 ). Based on experimental results, Kandouz and colleagues propose that EPHB2 may affect autophagy via the ERK1/2 and PI3K pathways ( 27 , 30 ). Moreover, they observed LC3 accumulation and transformation from LC3I to LC3II in EPHB2-upregulated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Du et al identified autophagy-related genes whose differential expressions are linked to breast tumors and constructed autophagy-related gene signatures with great prognostic value [422]. In addition, autophagy-related long non-coding RNAs (lncRNAs) have been identified as signatures for cancer prognosis and treatment targets, especially in breast, lung, and colorectal cancer [423][424][425][426][427][428][429][430][431]. Moreover, autophagy-related non-coding RNAs have also contributed to diagnosing and treating cardiovascular diseases [432,433].…”
Section: Autophagy In Health and Diseasementioning
confidence: 99%